Decentralized Device Authentication for Cloud Systems with Blockchain Using Skip Graph Algorithm - Sammy, F.; Vigila, S. Maria Celestin (Computer Assisted Methods in Engineering and Science; Vol 30 No 2 (2023), 2022)
Cloud computing provides centralized computing services to the user on demand. Despite this sophisticated service, it suffers from single-point failure, which blocks the entire system. Many security operations consider this single-point failure, which demands alternate security solutions to the aforesaid problem. Blockchain technology provides a corrective measure to a single-point failure with the decentralized operation. The devices communicating in the cloud environment range from small IoT devices to large cloud data storage. The nodes should be effectively authenticated in a blockchain environment. Mutual authentication is time-efficient when the network is small. However, as the network scales, authentication is less time-efficient, and dynamic scalability is not possible with smart contract-based authentication. To address this issue, the blockchain node runs the skip graph algorithm to retrieve the registered node. The skip graph algorithm possesses scalability and decentralized nature, and retrieves a node by finding the longest prefix matching. The worst time complexity is O (log n ) for maximum n nodes. This method ensures fast nodal retrieval in the mutual authentication process. The proposed search by name id algorithm through skip graph is efficient compared with the state-of-art existing work and the performance is also good compared with the existing work where the latency is reduced by 30–80%, and the power consumption is reduced by 32–50% compared to other considered approaches.